Analysis of Risk Management Model Simplification for Food and Beverage Industry through Small Business and Ventures - Eldian Rinaldi; Luh Kemala Putri Widhiari; I Nyoman Hendra Laksmana (CV. ULIL ALBAB CORP, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are firms with assets and annual sales of up to Rp500 million that are held by individuals, families, or commercial groups. However, the failure rate is significant, and some MSMEs fail to survive. The concept of risk management detailed a collection of activities by recognizing issues, mapping prospective risks to determine the hazards that presently exist in the business, and forecasting possible risks that may develop in the future. Based on these principles, the majority of research respondents in Bandung, Jawa Barat are micro, small, and medium-sized food and beverages business owners. Using a questionnaire, the brand name and owner's age, educational background, expected gross profit, and understanding of the risk management concept are gathered. validity and reability ab are utilized to accomplish the data analysis. The analysis based on 0.729 performed by KMO-Bartlett. 33.849%, 15.600 % for Factor 2 among 5 variables because the value is bigger than 1. As those factor could be described as 37,276% for F1 and 65,817% for F2. The factor loadings resulting from the communalities are used as scoring to generate a recommended solution in the approach of a risk mitigation plan, while the risk action and monitoring plan is utilized for the implementation plan. The goal of the research is to develop a proposed solution for business improvement in MSMEs by handling the business issue with a risk management approach, which entails identifying the business issue, conducting an assessment to know the severity of the issue, determining the treatment, initiatives and strategies to overcome the issue, and determining a monitoring plan as a step of evaluation and improvement continuously because risk management is a continuous process to create sustainable businesses. As the research is conduct in the manufacture and trade, food & industry sector there are 7 industries that left and the research could also implemented in another region, cities and country.